Soil nematodes in an arable field and a fallow – density and diversity - Ilieva-Makulec, Krassimira; Franczak, Renata; Makulec, Grzegorz (Studia Ecologiae et Bioethicae, 2011)
The results presented here concern the study, which was carried out in spring 2009 on an arable field and a fallow. The following parameters were analyzed: density, taxonomic composition, trophic and dominance structure of soil nematode communities. Shannon-Weaver diversity index, Sørensen’s index of similarity, and Maturity index were also calculated. The results show that the nematode community in the soil of arable field differed from that on the fallow in respect of density and trophic structure. Nematode density was higher in the arable soil than in the fallow. The group of bacterial-feeding nematodes was the most numerous among five trophic groups recorded in the study. The higher density of that group in the arable soil than in the fallow indicates the positive response of bacterial-feeding nematodes to the higher nutrient supply after the manure applying. The results show that in three years of fallow nematode communities became more mature and diverse than in the arable soil. The study confirms the indicative value of some nematode community parameters and indices for the assessment of the varying human intervention and the functional state of the soil.